The Effect of Grit and Gratitude on Subjective Well-Being of Students Attending Limited Face-to-Face Learning - Natalia, Christina Edo; Lestari, Angelina Kartini Agung; Cahyasari, Emanuela Adika; Cindrawan, Restalia; Matutina, Allin Yosephina; Sumargi, Agnes Maria (Proceeding International Conference on Religion, Science and Education, 2022)
The decline in the number of Covid-19 cases and the wide implementation of vaccination programs in Indonesia have made the enforcement of the Restrictions on Community Activities (PPKM) to be lowered to alert level 1 for some regions in Indonesia. This has led schools to use hybrid learning that provides opportunities for students to attend face-to-face learning at schools. Students need to adjust with the current condition, and therefore, their subjective well-being might be influenced. Notably, students’ subjective well-being is important as it determines students’ academic and life outcomes. The two factors that might influence students’ subjective well-being were grit and gratitude. This study aimed to examine the influence of grit and gratitude on subjective well-being of students attending face-to-face learning during the Covid-19 pandemic. Participants were 66 middle- and high-school students in some regions in Indonesia who voluntarily completed the questionnaire 12-Grit Scale, Gratitude Questionnaire (GQ-6), and Student Subjective Well-being Questionnaire. Multiple regression analysis showed that only gratitude was the best predictor of students’ subjective well-being. Gratefulness enhanced students’ subjective well-being but grit was not a significant predictor for students’ subjective well-being perhaps because students perceived offline learning was difficult, making them unable to focus and enjoy the ongoing learning process. Students might also perceive that teachers did not provide sufficient support to their learning. Therefore, having perseverance and passion (grit) alone is not enough to make students overcome this condition, and make them feel happy with the learning process. As gender and education level might also influence students’ subjective well-being, further studies need to consider these factors.